2013
DOI: 10.1038/cddis.2013.410
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A: a key player for human disease

Abstract: Cyclophilin A (CyPA) is a ubiquitously distributed protein belonging to the immunophilin family. CyPA has peptidyl prolyl cis-trans isomerase (PPIase) activity, which regulates protein folding and trafficking. Although CyPA was initially believed to function primarily as an intracellular protein, recent studies have revealed that it can be secreted by cells in response to inflammatory stimuli. Current research in animal models and humans has provided compelling evidences supporting the critical function of CyP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
374
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(384 citation statements)
references
References 123 publications
7
374
1
2
Order By: Relevance
“…Cyclophilin, a member of the immunophilins found in all the organisms, including prokaryotes and eukaryotes, is known to be the intracellular receptor of the immunosuppressive drug cyclosporine A (CsA) (2)(3)(4). In humans, seven major cyclophilins (from a total of 16 cyclophilins) are expressed, viz., CypA (18 kDa), CypB (22 kDa), CypC, CypD, CypE, Cyp40 (40 kDa), and CypNK (first identified from human natural killer cells).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophilin, a member of the immunophilins found in all the organisms, including prokaryotes and eukaryotes, is known to be the intracellular receptor of the immunosuppressive drug cyclosporine A (CsA) (2)(3)(4). In humans, seven major cyclophilins (from a total of 16 cyclophilins) are expressed, viz., CypA (18 kDa), CypB (22 kDa), CypC, CypD, CypE, Cyp40 (40 kDa), and CypNK (first identified from human natural killer cells).…”
Section: Introductionmentioning
confidence: 99%
“…35 For the first time, we show that PPIA is downregulated in the context of FLG deficiency and in AE skin (Figs 3, 5, and 6), suggesting that PPIA might represent a novel disease mechanism downstream of FLG. Interestingly, PPIA is the cytoplasmic binding partner of cyclosporine, an effective therapeutic in patients with AE.…”
Section: Discussionmentioning
confidence: 64%
“…39 No concurrent reduction in PPIA mRNA expression was observed in shFLG LSEs (Fig 5, C); the reduction in intracellular protein expression might instead reflect an increase in PPIA secretion known to be triggered after inflammatory/stress stimuli in epithelia. 35 Extracellular PPIA functions as both a proinflammatory stimuli (autocrine/paracrine) and potent chemoattractant of CD147 1 immune cells. 35,40 Stress and inflammatory pathways were overrepresented in our data set after FLG knockdown (Fig 4), and keratinocytes are known to secrete the close family member cyclophilin B and to express CD147 cell-surface receptors, 41 suggesting that similar regulation of PPIA might occur within the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al [30] demonstrated the synergic role of HBV in increasing cellular CypA and its action in HBsAg secretion. As mentioned previously [21], CypA has a key role in life cycle and pathogenesis of several viruses, such as Human Immunodeficiency virus type 1(HIV-1), Hepatitis C virus (HCV), and HBV. It could be suppressed by CypA inhibitors (Alisporivir, NIM811), which their anti-HCV activities studied previously [15,27].…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed that the interaction energy of HBF-0259 to CypA (-545.41 kcal/mol) was obviously higher than Annexin II and Rab7 (Table 3). CypA is a peptidyl-proline cis to trans isomerase in the cells and is believed to have a role in the pathogenesis of some diseases [5,21] which make it a potent molecule for therapeutic approaches [22]. Tian et al [30] demonstrated the synergic role of HBV in increasing cellular CypA and its action in HBsAg secretion.…”
Section: Discussionmentioning
confidence: 99%